Nutrition of pigs kept under low and high sanitary conditions : - Meer, Yvonne van der (Wageningen University, 2017)
The objective of the present thesis was to study the effect of low and high sanitary conditions (HSC) on amino acids and energy metabolism in pigs. Also, interactions between the immune system, nutrient metabolism and damaging behaviour of pigs were considered in this thesis.